Trajectories of frailty and related factors of elderly people in Mexico - Rojas Huerta, Abigail Vanessa (Población y Salud en Mesoamérica, 2022)
Introduction. Frailty is an indicator of health status in old age and a common clinical syndrome in older adults that carries an increased risk of poor health outcomes, including falls, incidents of disability, hospitalization, and mortality. This study aimed to identify the different trajectories of frailty and the factors related to frailty among Mexican older adults over time. Methods: Data are from a four-wave panel composed of older Mexican adults from 2001 to 2015 of the Mexican Health and Aging Study (MHAS). Frailty is the accumulation of deficits using a frailty index. A multilevel analysis, using hierarchical models, was applied to know the changes of frailty trajectories and what factors are related to it. Results. Being female, older, being widowhood, and having a lower level of education were risk factors for having a high frailty index and lower financial satisfaction doing activities at home have adverse effects. Conclusion. The findings of this work present information about the prevalence of frailty considering the proportion of deficits that individuals possess and their main associated components in older Mexican adults. It is necessary to improve socioeconomic health conditions in phases before old age to avoid developing frailty in the future.